Respuesta :

Answer:

36

Step-by-step explanation:

[tex] {x}^{2} - 12x + c \\ = {x}^{2} + 2 \times x \times 6 + {6}^{2} \\ = {x}^{2} - 12x + 36 \\ equating \: it \: with \: \\ {x}^{2} - 12x + c \\ c = 36[/tex]

Answer:

36.

Step-by-step explanation:

If you want to make a perfect square trinomial, you want to do -12 / 2 = -6. That way, you know that the c should be (-6)^2 = 36.

So, you have x^2 - 12x + 36, which is equal to (x - 6)^2, which is equal to x^2 - 6x - 6x + 36, which is equal to x^2 - 12x + 36.

Hope this helps!